Ultra mare in servicio domini regis: English barons and the defence of Normandy, 1194–1204. Issue 264 (18th April 2021) - Hopkinson, Nick
Abstract: This article analyses the provision of military service by English barons in the wars in Normandy between 1194 and 1204, a topic that has not previously been examined in any depth. It demonstrates that an important section of the English baronage provided regular military service in Normandy, driven by their own personal interests in the duchy and the pursuit of royal favour and rewards. It concludes that these barons were not fundamentally opposed to providing service overseas, and that this was not a factor in the loss of Normandy, but became an important political lever in their conflict with King John.